Effect of dialysis modality on kidney transplant outcomes in South Africa: a single-centre experience - Boosi, Reese; Dayal, Chandni; Chiba, Sheetal; Khan, Fatima; Davies, Malcolm (African Journal of Nephrology, 2025)
Background: The effect of dialysis modality on transplant outcomes is disputed, with reduced long-term graft survival in patients receiving peritoneal dialysis reported in some studies. Resource constraints in South Africa limit patient choice of modality, with most state-funded units pursuing a policy of “peritoneal dialysis first”. Application of transplant eligibility as an entrance criterion for dialysis in these settings requires analysis of the effect of modality on transplant outcomes. We therefore undertook the first South African analysis of the effect of antecedent dialysis modality on the development of delayed graft function, rejection and graft function at long-term follow-up. Methods: A retrospective review of all kidney transplants at Charlotte Maxeke Johannesburg Academic Hospital between 1 January 2006 and 31 December 2011 was undertaken. Graft outcome parameters (development of delayed graft function, graft function as indicated by eGFR, development of rejection, and graft survival) were compared between peritoneal dialysis (PD) and haemodialysis (HD) modalities using logistic regression and Cox proportional hazard modelling. Results: Delayed graft function was more frequent in HD than PD recipients (66% versus 34%, P = 0.004); HD increased the odds of DGF independently of donor type (OR 3.82, 95% CI 1.46–9.99, P = 0.006). Graft function as indicated by eGFR was comparable between HD and PD subgroups on follow-up. Rejection was numerically more frequent in PD recipients (49% versus 35%, P = 0.135); PD was associated with an increased risk of rejection over 10-year follow-up (HR 3.32, 95% CI 1.40–7.91, P = 0.007). Overall, graft survival was not dissimilar between dialysis modalities (P = 0.737). Conclusions: Haemodialysis may increase the risk of delayed graft function, possibly due to haemodynamic aberrations associated with this modality, as reported elsewhere. Peritoneal dialysis appears to be associated with increased risk and earlier occurrence of rejection, consistent with previous studies, suggesting accelerated immune reconstitution in this modality. Despite these associations, no effect was observed for dialysis modality on long-term graft function or survival, mirroring previous findings from the developed world.